2022
DOI: 10.1097/bpo.0000000000002001
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Patients Are 40% More Likely to Get a Cast Injury

Abstract: Background: Cast injuries can occur during application, throughout immobilization, and during removal, with common morbidities being pressure ulcers and cast saw burns. The incidence rate of cast injuries in generalized and diagnosis specific pediatric populations is not known. The goal of this study is to accurately quantify the rate of incidence of cast injuries at a large pediatric orthopaedic practice and identify potentially modifiable risk factors to guide quality of care improvement. Methods: A retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The majority of device-related pressure injuries were of the heel (58%) and were primarily owing to casts, while those of the knee or calf (33%) were primarily owing to knee immobilizers. A recent study found that pediatrics patients with a neuromuscular diagnosis had a significantly higher incidence of cast-related injuries (pressure injuries and saw burns) compared with those without 19. Therefore, it is important to have increased suspicion of heel pain in postoperative neuromuscular patients with lower extremity casts and establish routine skin checks and protective padding over bony prominences for those children wearing postoperative knee immobilizers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of device-related pressure injuries were of the heel (58%) and were primarily owing to casts, while those of the knee or calf (33%) were primarily owing to knee immobilizers. A recent study found that pediatrics patients with a neuromuscular diagnosis had a significantly higher incidence of cast-related injuries (pressure injuries and saw burns) compared with those without 19. Therefore, it is important to have increased suspicion of heel pain in postoperative neuromuscular patients with lower extremity casts and establish routine skin checks and protective padding over bony prominences for those children wearing postoperative knee immobilizers.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that pediatrics patients with a neuromuscular diagnosis had a significantly higher incidence of cast-related injuries (pressure injuries and saw burns) compared with those without. 19 Therefore, it is important to have increased suspicion of heel pain in postoperative neuromuscular patients with lower extremity casts and establish routine skin checks and protective padding over bony prominences for those children wearing postoperative knee immobilizers. Furthermore, preventive measures such as educating health care providers to provide heel padding in lower leg casts particularly in the immediate postoperative period when edema is present, have been shown to decrease rates of cast-associated skin injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Cast problems in children with neuromuscular conditions were presented at the 2022 American Academy of Orthopaedic Surgery (AAOS) Annual Meeting. 18 They found 14/28 cast injuries were in children with a neuromuscular diagnosis and all were pressure ulcers. There was no difference in who placed the cast (attending surgeon, resident, or cast tech) or where the cast was placed (operating room, clinic, or emergency room).…”
Section: Cast Complicationsmentioning
confidence: 99%
“…Researchers from Los Angeles (California, USA) therefore reviewed all their paediatric patients treated with a plaster cast over a 15-month period, recording the underlying diagnosis, the type of cast, and the level of training of the plaster technician. 4 Injuries were identified from contemporaneous records made at the time of cast removal. Overall, 2,239 casts were placed on children over this period with a total of 28 injuries recorded, giving an incidence rate of 12.5 per thousand.…”
Section: Neuromuscular Patients Are 40% More Likely To Get a Cast Injurymentioning
confidence: 99%